The “Blind Spot” of Plagiarism: A Study on Plagiarism in the Articles Submitted to Birat Journal of Health Sciences - Chhetri, Prabin; Rimal, Hem Sagar; Kafle, Santosh Upadhyaya; Kafle, Tara Kumari (Birat Journal of Health Sciences, 2020)
Introduction: The word plagiarism, in literature, means stealing someone’s works without acknowledging the author. It is an unavoidable fact that an article has to be original when it is presented for publication. Often it is seen that during the research works, authors put lot of effort in collecting the facts and figures for their article but they seem to have a blind spot when it comes to plagiarism. The detection of the plagiarism is a challenging and time consuming task for most of the journals. Objectives: The objective of the study is to understand the level of plagiarism in the articles submitted in Birat Journal of Health Sciences. Methodology: A descriptive cross-sectional study was conducted on plagiarism by retrieving the data of articles submitted to Birat Journal of Health Sciences (BJHS), an official medical journal of Birat Medical College (BMC), from April 2017 to August 2018. Total 111 articles were examined through the iThenticate Software, a commercial Plagiarism Detection Tool (PDT) Version 2.0.8. Articles were analyzed using descriptive statistics. Result: It was found that 63 (56.75%) articles were found to be less than 20% plagiarized and 48 (43.22%) articles were found above the cut-off point (20% plagiarized) putting them in the category of plagiarized article. Conclusion: It was found that the incidence of plagiarism in the articles submitted to BJHS was very common. It is also evident from the study that a commercial plagiarism detection tool (PDT) can be a very useful tool for detecting and preventing plagiarism in the articles. It was also noticeable to find that the articles of clinical consultants(who are not associated with academic institutions) had higher level of plagiarism in their articles in comparison to the academicians (who are associated with academic institutions).